Three different pathways of IgM-antibody-dependent hemolysis are mainly regulated by complement - Bartolmäs, Thilo; Pruß, Axel; Mayer, Beate (Frontiers in Immunology, 2023)
Antibodies to red blood cells (RBCs) may destroy erythrocytes via Fc-mediated phagocytosis or complement-dependent hemolysis. Complement activation on RBCs can be detected by C3d-direct antiglobulin test (DAT), which is the only test in immunohematology that directly targets complement. However, a positive DAT with anti-C3d cannot distinguish between C3b-mediated extravascular hemolysis, C5b-C9-mediated intravascular hemolysis and C5b-C8-mediated eryptosis. Furthermore, the DAT is not suitable to estimate the strength of hemolysis. Autoimmune hemolytic anemia (AIHA) is a rare disease that is caused by autoantibodies (aabs) to RBCs that is divided into warm AIHA and in cold agglutinin disease (CAD). The causative antibodies in CAD and sometimes in warm AIHA are from the IgM class. Depending on strength of complement activation they can induce extravascular hemolysis, intravascular hemolysis and eryptosis. We studied the three types of hemolysis by use of sera from patients with CAD under various conditions. We found that additionally to the routinely applied C3d-DAT, indirect tests for complement activity (free hemoglobin and Annexin V-binding to phosphatidylserine-exposing RBCs) should be used to determine the portion of extravascular, intravascular and eryptotic hemolysis. Eryptotic hemolysis may be a significant contributor to clinically relevant CAD or IgM warm AIHA, which should be considered for successful treatment.